2018
DOI: 10.1186/s41038-017-0105-9
|View full text |Cite
|
Sign up to set email alerts
|

An objective measure for the assessment and management of fluid shifts in acute major burns

Abstract: BackgroundMajor burns are life threatening. Fluid resuscitation is required for survival to maintain intravascular volumes and prevent hypovolemic shock. Bioimpedance spectroscopy (BIS) has been recognised as a potential method of monitoring fluid shifts after burn and in other disease states. The aims of this study were to examine the reliability of BIS across different dressing conditions and electrode positions, establish the influence of Acticoat™ on BIS variable measures and determine the validity of whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The invasive or cost- and time-intensive nature of many of these methods, however, likely hinders their implementation into clinical practice. Other novel and promising methods that have been developed for the use in the ICU setting are bioelectrical impedance and musculoskeletal ultrasound [ 69–71 ]. Both are practical, non-invasive, bedside tools that have shown to be valid and related to a variety of clinical outcomes, such as mortality and morbidity in critically ill adults [ 72–80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The invasive or cost- and time-intensive nature of many of these methods, however, likely hinders their implementation into clinical practice. Other novel and promising methods that have been developed for the use in the ICU setting are bioelectrical impedance and musculoskeletal ultrasound [ 69–71 ]. Both are practical, non-invasive, bedside tools that have shown to be valid and related to a variety of clinical outcomes, such as mortality and morbidity in critically ill adults [ 72–80 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of instruments that can be utilised to measure the components of the concept of burn care. For example, fluid status can be evaluated by using bioimpedance spectroscopy (BIS) (63). The visual analog and numeric rating scales are helpful to assess pain in patients with burn (64).…”
Section: Define Empirical Referentsmentioning
confidence: 99%
“…Transpulmonary thermodilution is one such noninvasive method that has been validated in burns [14]. Other methods include extra-vascular lung water, intrathoracic blood volume, pulse contour cardiac output (PiCCO), arterial waveform monitoring (LiDCO) devices and bioimpedance spectroscopy [1,12,15,16] (Figure 1). However, certain studies have shown that use of arterial waveform monitoring devices such as LiDCO systems had lower fluid requirement than what was calculated by Parkland formula [12,17].…”
Section: Goal-directed Fluid Therapy and Haemodynamic Monitoringmentioning
confidence: 99%